PROPOSED MARKETING STRATEGY FOR LOGISTICS SERVICE PROVIDER (A CASE STUDY : PT. SEMBRANI MUKTI TRANS) - Yasinta Putri, Silvana
Known as the largest economy in Southeast Asia, Indonesia transportation and logistics sector plays a very important role and it is one of the most influential for economy. In this digitalization era, there are an increasing number of micro, small, and medium-size enterprises (MSMEs) and Small Medium-sized Enterprises (SMEs) that has been starting to do the marketing and promotion their product through online media market place. Moreover, e-commerce as a online media market place is growing currently. It generates the higher demand for logistics service provider to deliver the products. The improvement and new innovation in technology in this digitalization era also generates the start up company which offers the logistics service delivery. Therefore, it will be the threats and opportunities for PT. Sembrani Mukti Trans. Currently, PT. Sembrani Mukti Trans is still facing the issue that the sales growth has not been increased significantly since the company was established in 2010 caused by lack of marketing strategy. While, currently the market segment is increased and getting better. This research uses qualitative research method, which assessing through the external analysis and internal analysis. The external analysis is conducted by the PEST Analysis, Porter’s Five Force, and Competitor Analysis. While, the internal analysis uses STP Analysis, Marketing Mix 7Ps, and Business Model Canvas. The SWOT Analysis and Root Cause Analysis are also conducted to identify the business issues of the company deeply. This research also uses the questionnaire to gain information from the potential customer and interview to gain information and feedback from the existing customer. To solve the problem, it can be proposed the solution which can be obtained from TOWS Matrix and the solution that can be implemented to the new Marketing Mix and new Business Model Canvas based on the analysis, questionnaire, and interview that has been conducted. There are several solution that can be implemented, those are developing new product, developing product innovation, developing more partnership with other Logistics Service Provider, looking for investor, create website, provide branch office, develop new pricing strategy, conducting the offline promotion, conducting the online promotion, hiring the digital marketing specialist, improving the customer service and driver performance, providing the online system process, providing online tracking system, and improving the personal look of driver.